Ethical issues in neuroscience - Fuchs, Thomas (Current opinion in psychiatry, 2006)
Purpose of review - The study gives an overview of ethical questions raised by the progress of neuroscience in identifying and intervening in neural correlates of the mind. - Recent findings - Ethical problems resulting from brain research have induced the emergence of a new discipline termed neuroethics. Critical questions concern issues, such as prediction of disease, psychopharmacological enhancement of attention, memory or mood, and technologies such as psychosurgery, deep-brain stimulation or brain implants. Such techniques are capable of affecting the individual's sense of privacy, autonomy and identity. Moreover, reductionist interpretations of neuroscientific results challenge notions of free will, responsibility, personhood and the self which are essential for western culture and society. They may also gradually change psychiatric concepts of mental health and illness. These tendencies call for thorough, philosophically informed analyses of research findings and critical evaluation of their underlying conceptions of humans. - Summary - Advances in neuroscience raise ethical, social and legal issues in relation to the human person and the brain. Potential benefits of applying neuroimaging, psychopharmacology and neurotechnology to mentally ill and healthy persons have to be carefully weighed against their potential harm. Questions concerning underlying concepts of humans should be actively dealt with by interdisciplinary and public debate.
Gesehen am 17.12.2020